2021
DOI: 10.1128/mbio.03075-21
|View full text |Cite
|
Sign up to set email alerts
|

The Cellular and Viral circRNAome Induced by Respiratory Syncytial Virus Infection

Abstract: Noncoding RNAs (ncRNAs) demonstrate substantial roles in cell-virus interactions. Circular RNAs (circRNAs) are a newly identified class of ncRNAs that have gained increased attention recently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…In-depth sequence analyses of each back-splicing site revealed the production of canonical and noncanonical viral circRNAs processed by the U2-dependent or U2-independent splicing machinery, respectively. Therefore, this report provides new information on the production of noncanonical circRNAs during viral infection ( 6 , 25 , 26 ). The next set of experiments was based on open and unbiased analyses of lymphoma-derived sequences over the whole MDV genome and pointed out the meq and LATs loci as the central hubs of viral circRNA expression during tumorigenesis.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In-depth sequence analyses of each back-splicing site revealed the production of canonical and noncanonical viral circRNAs processed by the U2-dependent or U2-independent splicing machinery, respectively. Therefore, this report provides new information on the production of noncanonical circRNAs during viral infection ( 6 , 25 , 26 ). The next set of experiments was based on open and unbiased analyses of lymphoma-derived sequences over the whole MDV genome and pointed out the meq and LATs loci as the central hubs of viral circRNA expression during tumorigenesis.…”
Section: Discussionmentioning
confidence: 94%
“…However, only a few viruses have been shown to encode their circRNAs. Most of the viral circRNAs have been identified in the Herpesviridae family ( 6 , 21 , 22 ) but some circRNAs are produced by other DNA virus families, such as the Papillomaviridae ( 23 ) and Polyomaviridae ( 24 ) or RNA viruses, e.g., Coronaviridae ( 25 ) or Paramyxoviridae ( 26 ). Former functional studies on herpesvirus-encoded circRNAs have suggested roles in immune evasion and cancer development ( 27 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…CircRNAs are an alternative splicing product and thus expand the number of transcripts without extending genome size; a strategy that may be advantageous for organisms with limited coding space. In line with this hypothesis, recent studies have experimentally confirmed viral circRNAs expressed by beta-and gamma-herpesviruses, human papillomavirus, Merkel cell polyomavirus, hepatitis B virus, respiratory syncytial virus, and coronaviruses; with bioinformatic evidence for many other viruses (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 79%
“…Currently, research on viral circRNAs is primarily focused on DNA viruses. Only a few RNA viruses have been reported to produce circRNAs, including respiratory syncytial virus, 26 MERS-CoV, 27 SARS-CoV-1, 27 SARS-CoV-2, 27 Bombyx mori cypovirus (BmCPV), 28 murine hepatitis virus, 29 and grass carp reovirus. 30 Among the aforementioned RNA viruses that can produce circRNAs, only the function of the BmCPV circRNA has been revealed.…”
Section: Introductionmentioning
confidence: 99%